Effects of intermittent mixing mode on solid state anaerobic digestion of agricultural wastes. (June 2020) - Wang, Yaya; Zhang, Jiaxing; Sun, Yanbo; Yu, Jiadong; Zheng, Zehui; Li, Shuyan; Cui, Zongjun; Hao, Jianjun; Li, Guoxue
Abstract: This study investigated the effects of three different intermittent mixing modes (top, middle and bottom) on the performance of solid state anaerobic digestion (SS-AD) process of pig manure, corn stover and cucumber residues in a stirred tank reactor (STR). Results showed the cumulative methane yields of reactors had similar values ( P >  0.05) except for the unmixed reactor (CK), which had a very low methane production. Reactors of top-mixed (T1) had shortest technical digestion time (T80 ) and more stable physicochemical characteristics than the other treatments. These findings indicated the three mixing modes had almost no effect on the cumulative methane yields, but affected the digestion process. The main bacteria in T1 reactor was Clostridium_sensu_stricto_1 . However, Caldicoprobacter accounted for a relatively large proportion of the bacteria in middle-mixed (T2) and bottom-mixed (T3) which was consistent with the later methane production than T1. Methanosarcina was the dominant archaea in T1 reactor. Methanoculleus and Methanosarcina were the main microorganisms in top and bottom area of T2 and T3 reactor. Acidogenic (top area) and methanogenic zones (bottom area) were formed in all reactors respectively, by combining the physicochemical properties and microorganisms. Overall, T1 showed more advantages for methane production during SS-AD. Highlights: Partial mixing affected AD process rather than methane yields. Reactors without any mixing failed with propionic acid inhibition. Partial mixing resulted in the differently spatial distribution of microorganisms. Mixing at top accelerated the methanogenesis process compared with others. Acidogenic (top area) and methanogenic zones (bottom area) were formed in reactors.